KEWIRAUSAHAAN KEPALA SEKOLAH - Iswadi Iswadi Iswadi (UNIVERSITAS BENGKULU, 2016)
The objectives of this study are to describe the school principal entrepreneurship competence in public senior high school I Ketahun, North Bengkulu. The method of this study was a descriptive qualitative. The data collecting by documentation, observation, interview and questionnaire. The results of the study; (1) in innovative dimensions were to complete the facilities and life skill graduated; (2) in hard work dimension by the team work focused, personnel development, and using standarized as outputs; (3) motivation dimension described ready for challenge, develop of school, giving the reward and punishment; (4) the best solution described ways by promoting and using information of technology. (5) to manage of unit production or service by placed the according personnel.Keywords: entrepreneurship, School Principal, Competence.